Constructivist teaching by heart : a child-centered approach for educators, PreK-3 - Calvert, Krista; McMillan, Dana (New York, NY : Routledge, 2024)
"This insightful book offers a modern take on the time-honored tradition of developmentally appropriate, child-centered, constructivist philosophy of instruction: Teaching children one at a time, yet all at once. The book provides a comprehensive road map to teaching that supports student engagement, child development, classroom environment, grouping and organization, authentic literacy instruction, and culturally informed practices. Through a series of practical chapter essays and examples, the authors push back against scripted curriculums and 'one-size-fits-all' school initiatives, offering instead rich examples and guiding questions to bring you closer to an authentic teaching approach that honors students and their learning. Designed for early childhood through third-grade teachers, principals, administrators, and pre-service students, Constructivist Teaching by Heart is essential reading for professional development, peer discussions, university coursework, individual study, and everyone on the journey to making children the heart of their classrooms"--
Keywords: Early childhood education -- Curricula; Education, Elementary -- Curricula; Constructivism (Education); Student-centered learning; Child development; EDUCATION / Elementary; EDUCATION / Preschool & Kindergarten; EDUCATION / General